Impedance-computed tomography algorithm and system - Wexler, A.; Fry, B.; Neuman, M.R.
An electrical impedance-based method and apparatus for imaging the interior of a structure, such as a mineral or human body, having regions of differing impedance, are described. The technique involves impressing a number of excitation patterns on the body and measuring the resulting voltages at a number of sites. Because voltages need not be measured at current-injection sites, contact resistance problems are ameliorated. This impedance-computed tomography reconstruction process employs the solution of the Poisson equation and makes no assumptions of raylike behavior of the current flow paths. Results, based on computer-simulated data and real measurements, are presented. © 1985 Optical Society of America.
Keywords: ALGORITHM; COMPUTER ANALYSIS; COMPUTER ASSISTED TOMOGRAPHY; DIAGNOSIS; IMPEDANCE; NONBIOLOGICAL MODEL; NONHUMAN